Identification of 4-substituted 2-(4-x-2, 5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25X-NBOMe) and analogues by gas chromatography–mass spectrometry analysis of heptafluorobutyric anhydride (HFBA) derivatives. Issue 1 (2nd January 2016) - Lum, Benny J.; Brophy, Joseph J.; Hibbert, D. Brynn
Abstract : Gas chromatograms and E.I. mass spectra of the parent compounds and seven heptafluorobutyric anhydride derivatised, 4-substituted 2-(4-x-2, 5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamines (25X-NBOMe), (x = Br, Cl, Me, Et, I, NO2, SMe; X = B, C, D, E, I, N, T2), 2-(2, 5-dimethoxyphenyl)-N-[(2-methoxyphenyl)methyl]ethanamine (25H-NBOMe) and six other analogues are reported. Derivatisation allows determination of the mass of the molecular ion, and observation of characteristic fragmentation patterns. All the NBOMe compounds studied showed a McLafferty rearrangement in the E.I. mass spectrum that is diagnostic of a hydrogen atom that is six atoms removed from a π-bonded hetero-atom. The ease of this protocol makes this an important tool for the routine analysis of appropriately-structured new psychoactive substances in crime laboratories.